Colonization of carbapenem-resistant Klebsiella pneumoniae in a sink-drain model biofilm system. (25th June 2021) - Burgos-Garay, Maria; Ganim, Christine; de Man, Tom J.B.; Davy, Terri; Mathers, Amy J.; Kotay, Shireen; Daniels, Jonathan; Perry, K. Allison; Breaker, Erin; Donlan, Rodney M.
Abstract: Background: Sink drains in healthcare facilities may provide an environment for antimicrobial-resistant microorganisms, including carbapenemase-producing Klebsiella pneumoniae (CPKP). Methods: We investigated the colonization of a biofilm consortia by CPKP in a model system simulating a sink-drain P-trap. Centers for Disease Control (CDC) biofilm reactors (CBRs) were inoculated with microbial consortia originally recovered from 2 P-traps collected from separate patient rooms (designated rooms A and B) in a hospital. Biofilms were grown on stainless steel (SS) or polyvinyl chloride (PVC) coupons in autoclaved municipal drinking water (ATW) for 7 or 28 days. Results: Microbial communities in model systems (designated CBR-A or CBR-B) were less diverse than communities in respective P-traps A and B, and they were primarily composed of β and γ Proteobacteria, as determined using 16S rRNA community analysis. Following biofilm development CBRs were inoculated with either K. pneumoniae ST45 (ie, strain CAV1016) or K. pneumoniae ST258 KPC+ (ie, strain 258), and samples were collected over 21 days. Under most conditions tested (CBR-A: SS, 7-day biofilm; CBR-A: PVC, 28-day biofilm; CBR-B: SS, 7-day and 28-day biofilm; CBR-B: PVC, 28-day biofilm) significantly higher numbers of CAV1016 were observed compared to 258. CAV1016 showed no significant difference in quantity or persistence based on biofilm age (7 days vs 28 days) or substratum type (SS vs PVC). However, counts of 258 were significantly higher on 28-day biofilms and on SS. Conclusions: These results suggest that CPKP persistence in P-trap biofilms may be strain specific or may be related to the type of P-trap material or age of the biofilm.